Avaliação dos marcadores do metabolismo mineral ósseo em pacientes com Distrofia Muscular de Duchenne - Anna Carolina Dias Munaier Lages (2015)
Duchenne Muscular Dystrophy (DMD) is the most common and severe form of childhood muscular dystrophy. It is a progressive disease, caused by mutations in the dystrophin gene, culminating in progressive muscle weakness. Despite the rapid advance in genetics, this disease has no cure yet. Glucocorticoids (CG) are the mainstay of treatment and, although beneficial, act by suppressing bone formation. Bone health is an important part of the care of these patients and the reduction in bone mineral density (BMD) associated with increased fracture risk is the strongest evidence for degraded bone quality. Objectives: To evaluate bone mineral metabolism markers in children and adolescents with DMD by means of biochemical markers of bone formation and resorption and to evaluate bone mass by bone densitometry. Methodology: Twenty-nine children and adolescents with DMD were followed-up at the Pediatric Neurology Unit of the Hospital das Clínicas of UFMG and 13 healthy children and adolescents, which constituted the control group. Laboratory analysis included blood calcium, phosphorus, alkaline phosphatase, urea, creatinine, 25OH vitamin D and parathyroid hormone (PTH) measurements, and 24-hour urine collection for calcium, citrate, phosphate, and creatinine measurements. For statistical analysis patients and controls were matched for age and patients were divided into subgroups: wheelchair users and non-wheelchair users and users and non-users of corticosteroids. Results: Between wheelchair and non-wheelchair users a significant difference was observed for age, weight, height and presence of scoliosis. The presence of scoliosis was observed in 48.3% and the history of long bone fracture in 27.6%. Low serum levels of 25OH vitamin D, creatinine, serum alkaline phosphatase and urinary creatinine and citrate excretion were observed when patients and controls were compared. Higher serum phosphorus and phosphate tubular reabsorption (phosphate TP) levels were observed than controls. Between wheelchair and non-wheelchair users there was a significant difference for creatinuria (mg / kg / day) and phosphate TP, lower in the wheelchair group, and for PTH, with higher levels in the wheelchair. Among users and non-users of corticosteroids only PTH was significant, lower in the group of users. The study patients had a reduced lumbar spine BMD (CL) z-score compared to controls and no significant difference was observed between the subgroups. Negative correlation was observed between CL BMD a and creatatine citraturia mg / g in corticosteroid users, between CL BMC and serum phosphorus in the DMD group and between CL BMC and creatinine citraturia mg / g in the corticosteroid group. Conclusions: Patients with DMD had significant clinical and laboratory differences and an overall reduction in BMD compared with healthy controls. There was no significant difference between the group with history of CG use and the one without history. There were significant negative correlations between the evaluated bone sites and urinary citrate and creatinine excretion, which suggest involvement of this molecule in the bone health of these patients.